Ma'pakande To Matua: Studi tentang Penyebab Masyarakat Kristen Mareali Masih Mempraktikkan Ritual Ma’pakande To Matua - Kristanto Kristanto; Agustina Lantang (Publikasi dan UKI Press UKI Toraja., 2017)
Most of the community in Mareali are Christian but there are some people who still practice the teaching of local animist beliefs known as Aluk To Dolo (the way of anchestors) such as a ritual called ma’pakande to matua. The cause of the practicing ma’pakande to matua by the Christian community in Mareali becomes the reason to conduct this research. In this research applied qualitative method.The result of this research can be concluded that there are several causes so that the ritual of ma’pakande to matua is still practiced by the Christian community in Mareali, for instance the teaching of Aluk To Dolo cannot be separated from the tradition which forceful plait the life of the hereditary community in Mareali and it becomes a holistic philosophy of their life.The teaching of Aluk To Dolo is kept tight in memory and always appears in thoughts and actions. Ma’pakande to matua is one of the influences of that. The cause of that is the low of Christianity knowledge by the Christian community in Mareali due to the lack of the guidance and religious education carried out by the church. The other reason is the failed of the church to reject the role of Aluk To Dolo’s leader who involved in the religious activities of Christian community and also the failure of the tradition and religious leaders to comprehend the principle of pemali pabullei aluk tu tau as the principle of the Toraja society for long time ago.